2014
DOI: 10.1007/s00253-014-6047-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the pH on the itaconic acid production with Aspergillus terreus

Abstract: Itaconic acid is mainly produced with the filamentous fungi Aspergillus terreus. An increase in the pH during the production phase of the cultivation resulted in an increase in the itaconic acid concentration. The pH was raised by a single pH shift ranging from pH 4 to 6 or by a pH control to pH 3. Different lyes can be used for the pH shift, but ammonia solution has proven to be the best, because here the productivity does not drop after the pH shift. The highest itaconic acid concentration of 146 g/L was rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(90 citation statements)
references
References 14 publications
1
82
0
Order By: Relevance
“…There was no significant difference in the pattern of glucose utilization and IA production among these 3 strains and final IA concentration was between 87 and 91 g L −1 . Recently, Hevekerl et al [30] reported that when pH control to 3.0 was started after 2.1 days of cultivation of A. terreus DSM 23081 in a medium containing 180 g glucose L −1 , the IA concentration reached to 146 g L −1 with a productivity of 0.48 g L −1 h −1 and a yield of 0.81 mol mol −1 glucose which is an increase of 68% compared to the cultivation without pH control. After 2.1 days, the cultivation had entered the production phase and IA was already formed.…”
Section: Production Of Itaconic Acid By Aspergillus Terreusmentioning
confidence: 98%
“…There was no significant difference in the pattern of glucose utilization and IA production among these 3 strains and final IA concentration was between 87 and 91 g L −1 . Recently, Hevekerl et al [30] reported that when pH control to 3.0 was started after 2.1 days of cultivation of A. terreus DSM 23081 in a medium containing 180 g glucose L −1 , the IA concentration reached to 146 g L −1 with a productivity of 0.48 g L −1 h −1 and a yield of 0.81 mol mol −1 glucose which is an increase of 68% compared to the cultivation without pH control. After 2.1 days, the cultivation had entered the production phase and IA was already formed.…”
Section: Production Of Itaconic Acid By Aspergillus Terreusmentioning
confidence: 98%
“…Although the most significant progress in improving itaconic acid production is made by classical process optimization techniques until now (Hevekerl et al 2014), the construction of mutant strains by genetic engineering is also promising for improving the itaconic acid production. For example, overexpression of CAD in A. terreus LYT10 enhanced the itaconic acid production level by nearly 10 % in shake flasks, and the production stage was shortened by around 4 h at the pilot scale (35 m 3 fermentor) (Huang et al 2014b).…”
Section: Discussionmentioning
confidence: 99%
“…Since it has been reported that controlling pH is important for IA production (Hevekerl et al, 2014), we performed fed-batch fermentation in which a pH of 6.2, the pH optimum for CadA, was constantly maintained by the addition of ammonia solution. Although cell mass in the fed-batch fermentation steadily increased, reaching $60-fold that in flask culture, IA production was just twofold higher (Fig.…”
Section: Ia Production In M9 Supplemented With Glycerol and Citric Acidmentioning
confidence: 99%